2018
DOI: 10.1371/journal.pone.0202440
|View full text |Cite
|
Sign up to set email alerts
|

A novel homodimer laccase from Cerrena unicolor BBP6: Purification, characterization, and potential in dye decolorization and denim bleaching

Abstract: The white-rot fungus Cerrena unicolor BBP6 produced up to 243.4 U mL-1 laccase. A novel laccase isoform LacA was purified; LacA is a homodimer with an apparent molecular mass of 55 kDa and an isoelectric point of 4.7. Its optimal pH was 2.5, 4.0, and 5.5 when 2, 2’-Azinobis-(3-ethylbenzthiazoline-6-sulphonate) (ABTS), guaiacol, and 2, 6-dimethoxyphenol (2, 6-DMP) were used as the substrates, respectively. The optimal temperature was 60°C for ABTS and 80°C for both guaiacol and 2, 6-DMP. LacA retained 82–92% ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 44 publications
3
24
0
Order By: Relevance
“…Similar studies of Dassai et al gave 87.87% decolorization of acid orange 51 azo dye in 48 hr using Box–Behnken design . The findings are also in good agreement with the reports of Zhang et al wherein >80% decolorization of a wide range of dyes have been reported using same quantity of laccase . Contrary to previous findings, present investigation offers significant decolourization of selected dyes by crude laccase under normal culture conditions.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Similar studies of Dassai et al gave 87.87% decolorization of acid orange 51 azo dye in 48 hr using Box–Behnken design . The findings are also in good agreement with the reports of Zhang et al wherein >80% decolorization of a wide range of dyes have been reported using same quantity of laccase . Contrary to previous findings, present investigation offers significant decolourization of selected dyes by crude laccase under normal culture conditions.…”
Section: Resultssupporting
confidence: 92%
“…Laccase catalyzes oxidation of wide variety of organic and inorganic substrates, including mono‐di‐and polyphenols, amino phenols, methoxy phenols, aromatic amines, ascorbate, and so forth . Having such extraordinary abilities, laccases are found useful for several processes such as wood pulp delignification, dye decolorization, water purification, dechlorination, and as a catalyst for the manufacture of drugs and cosmetics . Laccases are also applied in food processing to improve the texture of dough during baking .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Laccases (benzenediol: oxygen oxidoreductase; E.C.1.10.32.) are multi-copper extracellular glycoproteins with molecular weight of 60 -80 kDa having 15 -20% carbohydrate content and are wide spread in bacteria, insects, lichen and plants apart from fungi of diverse ecophysiological groups [1,2]. Laccases possess strong oxidation potentials that allow catalysis of a broad range of substrates such as polyphenols, substituted phenols, diamines and some inorganic compounds [3].…”
Section: Introductionmentioning
confidence: 99%
“…During the past several decades, numerous laccases have been isolated and characterized, mainly from fungal species and a few types of bacteria [16][17][18]. Among the many different laccase types, fungal laccases seem to have more favorable properties for commercial applications than other plant and bacterial enzymes due to the high reduction potential of their type-1 copper [19].…”
Section: Introductionmentioning
confidence: 99%